An evaluation of the effectiveness of oral health workers training done by community dentistry interns in San Juan, Batangas (AY 2011-2012) - Aguilar, Camille A.; Ambat, Sandra Luz C.; Infante, Minette M.; Santos, Jessica K. Rebueno
INTRODUCTION. An Oral Health Workers (OHW) training was conducted for selected Barangay Health Workers (BHW) from the 4 clusters of San Juan, Batangas, This was part of the overall objective of improving access to oral health care for the community. The BHWs attended 3 half-day sessions of the oral health training. To pass this training, a written examination and actual tooth brushing activity on an articulator was made. This study evaluates the effectiveness of the OHW training a year after it was conducted using the Kirkpatrick model. It also aims to determine areas of the training that may need further improvement.
METHODS. Purposive sampling of all 50 OHWs was conducted. To participate, a written informed consent was distributed. The Kirkpatrick model was used to evaluate the effectiveness of the OHW training. Four levels of evaluation were conducted, namely: Level 1 (Reaction) to determine the attitude of the participants towards being OHWs using Focus Group Discussion; Level 2 (Learning) to assess the knowledge retained by the participants with the same written examination used last year; Level 3 (Behavior) to evaluate the behavior of the participants by assessing the change in oral hygiene practices thru a tooth brushing return demonstration on themselves and; Level 4 (result) to determine the OHW's assistance rendered for dental concerns of the community thru a review of records.
RESULTS. Only 30 out of the 50 OHWs participated in this study. This study disclosed that there were no written objectives for the OHW training. It was not made clear to the trainees what their roles and functions in the community would be after the training. Attending to the evaluation activity of majority (60%) of the OHWs is an indication of positive attitude. For Level 2, using Paired Sample T Test, only 17 of the 30 participants passed the written examination. Of the 17 OHWs who passed, 15 did not show any improvement in their test scores while 2 got a higher score. Behavior (Level 3) was evaluated by asking the OHWs to brush their teeth in front of the researchers to demonstrate knowledge and practice of proper tooth brushing. Sixty-three percent were enthusiastic and confident in performing the activity. There were only two dental records available for review for Level 4 implying that the training did not include records taking. Further analysis of the results using Pearson Chi-Square Test, Fisher Exact Test and Pearson Test for Correlation revealed that there are no correlations between the exam scores and age, behavior and attitude of the participants towards oral health. Software used for all the analyses was the SPSS.
CONCLUSION. Following the Kirkpatrick method of evaluation of effectiveness, it can be concluded that the OHW training was partially effective with Levels 1 Reaction (60%) positive attitude and 2 Learning (57%) passed the written examination. The training needs improvement for Level 3 Behavior (37%) which is the ability to brush their own teeth properly and Level 4 Results which is the ability to record dental consultations.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Community health aides--Training of